Money, Inflation and Growth Relationship: The Turkish Case - Bozkurt, Cuma (International Journal of Economics and Financial Issues, 2014)
There is a significant relation between inflation, which is known as an increase in the general level of prices in the broadest sense of the word, money and growth. While the course of the relationship between money supply and inflation is evident in general terms, an overall tendency related to the relationship between inflation and growth hasn’t been clarified. This paper examines money, inflation and growth relationship in Turkey by using cointegration test. For this purpose, 1999.2 – 2012.2 period is taken and quarterly data of money supply (M2), GDP, velocity of money and deflator are used. According to the results from this paper, money supply and velocity of money is a main determinant of inflation in the long run in Turkey. On the other hand, 1% decreases in income directly reduces inflation by 1%. Keywords: Money; Inflation; Growth; Cointegration Test; Turkey. JEL Classifications: E31; E50; F43